2019
DOI: 10.1093/femsec/fiz107
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric life of Salmonella requires flagella-driven motility and EPS-mediated attachment to organic matter and enables cross-kingdom invasion

Abstract: Salmonella is an established pathogen of the members of the kingdom Animalia. Reports indicate that the association of Salmonella with fresh, edible plant products occurs at the pre-harvest state, i.e. in the field. In this study, we follow the interaction of Salmonella Typhimurium with the model plant Arabidopsis thaliana to understand the process of migration in soil. Plant factors like root exudates serve as chemo-attractants. Our ex situ experiments allowed us to track Salmonella from its free-living state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In addition to temperature-dependent changes in metabolism and stress response, the proteomic analyses in this study indicate the temperature-dependent synthesis of flagellar and chemotaxis proteins enabling a directed motility and is of crucial importance for Salmonella virulence. Several studies revealed the involvement of flagella-mediated motility in Salmonella infection of mammalian and plant hosts ( 59 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to temperature-dependent changes in metabolism and stress response, the proteomic analyses in this study indicate the temperature-dependent synthesis of flagellar and chemotaxis proteins enabling a directed motility and is of crucial importance for Salmonella virulence. Several studies revealed the involvement of flagella-mediated motility in Salmonella infection of mammalian and plant hosts ( 59 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Swim agar plates were prepared with 0.3% (w/v) agar. Overnight cultures grown in LB were spotted on the swim agar plates and incubated at 26 °C for different time points 5 . The images of the plates were taken with an Olympus STYLUS VH520 camera.…”
Section: Methodsmentioning
confidence: 99%
“…Overnight cultures grown in LB were spotted on the swim agar plates and incubated at 26 °C for different time points. 5 The images of the plates were taken with an Olympus STYLUS VH520 camera. Strain ΔfliC/fljB was used as negative control (without flagella) and the strains ΔcsgD and ΔbcsA were used as positive controls (hypermotile).…”
Section: Quantification Of Biofilmmentioning
confidence: 99%
See 2 more Smart Citations